Effect of the applications of a biological formulation (Azotobacter salinestris, Bacillus amyloliquefaciens, Rhizophagus intraradices) on the yield of Allium cepa ‘Century’ - Mamani, E. (2019)
de Siguas, Arequipa Province, Peru. The concentrations used were 2, 4, and 6 kg ha−1 with 4 applications by means of impregnation to the transplant and via drench every 15 days. The statistical design was through a DBCA with factorial arrangement randomly distributed in four blocks. The tests used were the orthogonal contrast test and Duncan’s multiple comparison test (α = 0.05). The findings showed that the treatment concentrations of 4 kg ha−1 and 6 kg ha−1 resulted in a lower incidence of Fusarium oxysporum, at 6.71% and 9.36%, an ABCPE of 637.78 and 950.14 units, and an exportable yield of 66.34 t ha−1 and 65.42 t ha−1, respectively, displaying significant differences from the control. The first application was statistically significant to the treatments with the highest number of applications, showing a greater exportable yield of 67.54 t ha−1. The best interactions between concentrations and applications were 6 kg ha−1 with 1 application, 4 kg ha−1 with 2 applications, and 4 kg ha−1 with 1 application, with exportable yields of 70.66, 69.61, and 69.11 t ha−1, respectively.